2021
DOI: 10.1016/j.isci.2021.102226
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ce (Ⅲ) / Ce (Ⅳ) ratio of cerium oxide for antibacterial application

Abstract: Summary Antibiotics have been considered as effective weapons against bacterial infections since they were discovered. However, antibiotic resistance caused by overuse and abuse of antibiotics is an emerging public health threat nowadays. Fully defeating bacterial infections has become a tough challenge. In this work, cerium oxide was fabricated on medical titanium by thermolysis of cerium-containing metal-organic framework (Ce-BTC). Regulation of Ce (Ⅲ)/Ce (Ⅳ) ratios was realized by pyrolysis of Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
(28 reference statements)
1
29
0
Order By: Relevance
“…The binding energies and the separation between the two peaks at 5.70 ± 0.02 eV were close to the reported values. , According to deconvolution results, the Ti 2p spectrum of the 75 mol % CeO 2– x –TiO 2 particles was mainly caused by the Ti 4+ oxidation state and slightly contributed by the reduced species Ti 3+ , which is assigned to Ti 3+ 2p 3/2 and appears at a lower binding energy of 456.6 ± 0.02 eV (black arrow). The peaks located at 904.6, 885.6, and 880.8 eV corresponded to Ce 3+ and the peaks at 917.0, 907.5, 901.1, 898.4, 889.3, and 882.5 eV belonged to Ce 4+ . , By integrating high-resolution XPS spectra of Ce 3d, the contents of Ce 3+ were 44.1 and 36.8%, respectively, for CeO 2– x and 75 mol % CeO 2– x –TiO 2 particles (Figure S-1). The previous studies , have confirmed that nanoceria showed oxidase-like activity, which was attributed to the valence states of Ce 3+ and Ce 4+ , as well as oxygen vacancies.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The binding energies and the separation between the two peaks at 5.70 ± 0.02 eV were close to the reported values. , According to deconvolution results, the Ti 2p spectrum of the 75 mol % CeO 2– x –TiO 2 particles was mainly caused by the Ti 4+ oxidation state and slightly contributed by the reduced species Ti 3+ , which is assigned to Ti 3+ 2p 3/2 and appears at a lower binding energy of 456.6 ± 0.02 eV (black arrow). The peaks located at 904.6, 885.6, and 880.8 eV corresponded to Ce 3+ and the peaks at 917.0, 907.5, 901.1, 898.4, 889.3, and 882.5 eV belonged to Ce 4+ . , By integrating high-resolution XPS spectra of Ce 3d, the contents of Ce 3+ were 44.1 and 36.8%, respectively, for CeO 2– x and 75 mol % CeO 2– x –TiO 2 particles (Figure S-1). The previous studies , have confirmed that nanoceria showed oxidase-like activity, which was attributed to the valence states of Ce 3+ and Ce 4+ , as well as oxygen vacancies.…”
Section: Resultsmentioning
confidence: 96%
“…CeO 2 is drawing more and more attention in the biomedical industry thanks to its antioxidant, antibacterial, anticancer, and biocompatibility properties. , In addition, TiO 2 nanoparticles doped with CeO 2 display an improved photocatalysis and photoinduced hydrophilicity in the visible spectrum compared with the anatase TiO 2 with a band gap of 3.2–3.35 eV, which is attributed to the lower band gap (2.9–3.2 eV) of CeO 2. , Noteworthily, the Ce 3+ /Ce 4+ redox couple can easily switch between two states (CeO 2 ↔ CeO 2– x + x /2O 2 ), which is crucial for ceria nanoparticles manifesting catalytic activity, enzyme-like activities, and germ-killing. ,, CeO 2 nanoparticles with high Ce 3+ content usually have abundant oxygen vacancies, facilitating oxygen exchange and redox reactions. However, the antimicrobial activity and durability of Gram-positive bacteria remain to be revealed due to an ambiguous understanding of the antibacterial mechanism. ,,, In this work, CeO 2– x –TiO 2 films stabilized by the xanthan gum were prepared using a microstamping method with three different patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure 4d, Ce, Fe, O and C elements were homogenously dispersed in Ce‐BDC@Fe 3 O 4 nanozymes [3, 15]. The C 1s (Figure 4a) could be fitted with three peaks at 284.84 , 286.46 and 288.52 eV, which are assigned to the peak of C‐C, the amorphous carbon C‐O‐C and the carboxyl carbon O‐C = O, respectively [30]. As shown in Figure 4b, the peak with BE of 529.8 eV was attributed to lattice oxygen species and consistent with the characteristic peak of Ce 4+ ‐O.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the formation of ROS on the surface of CeO 2 nanoparticles has been linked to the acidity of the surrounding environment. In acidic conditions, the redox transition between Ce(III) and Ce(IV) has been shown to induce the rise in ROS level and thus, toxic effects against bacteria [35] as well as cancer cells [32]. In in vitro tests with normal mammalian cells and less acidic pH, no signi cant cytotoxicity of CeO 2 nanoparticles has been observed but instead, a protective, survival and growth promoting effect has been demonstrated [36,37].…”
Section: Introductionmentioning
confidence: 99%